Auto profile - Anumula, Srikar (Kansas State University, 2015)
Present times most of the applications allow users to set profiles and activate them manually. Also, there is no such application to alert the calling person automatically whenever we are busy in a meeting. Auto Profile is an application which addresses these issues. Using this application, a custom profile can be created and activated. The user of this application can create any number of custom profiles with their own timings depending on their requirements from the available set of ringer modes such as vibration, silent, normal modes. All these settings will be changed automatically when they define a profile and set it as active. Every profile can be scheduled according to their wish. Also, users can define how often and how long they would like to activate the selected profile. Auto Profile Switcher will recognize their profile based on the current time and it will apply the right profile at the right time according to the given settings. For instance, they can save a home profile and a work profile, and the application will automatically switch from one to other automatically, without any user action. It's also possible for the users to apply manually saved profile wherever they are. Also, the application allows users not to bother about the calls from important persons when they are in some important meeting or busy. Automatically profile is activated as scheduled and sends a respective alert to the caller according to the profile activated. Auto Profile application is user-friendly and easy to use. The proposed application is developed for the android platform, which is used to create custom profiles and make sure that the tasks are executed as scheduled. This relieves users as they do not need to bother about the calls when they are in some important meeting or busy. As this is a mobile application users can easily organize their action wherever they are with ease.
Keywords: Auto profile switcher; Mobile applications; Profile settings; Android platfomAuto profile; Computer Science (0984)